Efek Pemberian Ekstrak Buah Salak (Salacca zalacca) dalam menurunkan kadar glukosa darah pada tikus model Diabetes melitus - Olvie Syenni Datu; Julianri Sari Lebang; Elly Juliana Suoth (Jurnal MIPA, 2023)
Diabetes Mellitus is a chronic disease characterized by elevated blood glucose levels. Diabetes Mellitus is a global disease that affects 536.6 million people in the world and is predicted to increase to 643 million people in 2030 and 783.2 million people in 2045. Snake fruit is one of the fruits in North Sulawesi that has the potential to be developed. be an alternative to treatment. The aims of this study is was to examine the effect of snake fruit extract in rats with diabetes mellitus model. The study used 5 groups, negative control group was given NaCMC solution, the positive control group was given metformin and the treatment group was given snake fruit extract with concentrations of 10%, 20% and 40%. The parameters observed in this study were body weight and blood glucose profile. The study showed that the administration of snake fruit extract had a significant effect on blood glucose profiles and body weight with p < 0.05 and there were significant differences between each treatment group both in the glucose profile parameters and body weight of rats.